2017
DOI: 10.1080/10538712.2017.1323814
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics of Dependent Youth Who Have Been Commercially Sexually Exploited: Findings From a Specialized Treatment Program

Abstract: Commercial sexual exploitation of children has emerged as a critical issue within child welfare, but little is currently known about this population or effective treatment approaches to address their unique needs. Children in foster care and runaways are reported to be vulnerable to exploitation because they frequently have unmet needs for family relationships, and they have had inadequate supervision and histories of trauma of which traffickers take advantage. The current article presents data on the demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 9 publications
2
76
0
Order By: Relevance
“…Landers and colleagues recently described the mental health needs and trauma history among CSE youth receiving care in a specialized treatment program in Florida. They found that almost 87% of the youth reported a history of sexual abuse in their lifetime, 62% had depression, and almost 47% had evidence of substance use that appeared to interfere with functioning 26 . However, the youth surveyed were involved in an intensive trauma-informed therapeutic program for youth in the child welfare program, and not a specialty court system 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Landers and colleagues recently described the mental health needs and trauma history among CSE youth receiving care in a specialized treatment program in Florida. They found that almost 87% of the youth reported a history of sexual abuse in their lifetime, 62% had depression, and almost 47% had evidence of substance use that appeared to interfere with functioning 26 . However, the youth surveyed were involved in an intensive trauma-informed therapeutic program for youth in the child welfare program, and not a specialty court system 26 .…”
Section: Introductionmentioning
confidence: 99%
“…(Fraley & Aronowitz, 2019, p. 12)Vulnerability to CSEC victimization may also manifest in a child’s disengagement and deviant behavior, as evidenced by a study of CSEC victims ( N = 25) that revealed suspensions from school for more than half of the participants (Shaw et al, 2017). Landers and colleagues (2017; N = 87) support these findings; more than two thirds of CSEC victims exhibited moderate to severe behavior problems in school, thus risking expulsion, and about one third missed at least 2 days of school per week on average. Thus, while low educational attainment was not a strong risk factor for CSEC, academic difficulty, as well as behavior problems in school, was found to constitute noteworthy predictors of CSEC.…”
Section: Resultsmentioning
confidence: 72%
“…Similarly, in a study by Reid and colleagues (2015), in 58% ( n = 11) of 19 familial sex trafficking cases, the biological mother was the trafficker. In alignment with these findings, another study ( N = 87) found that about half of the family members were not supportive of the CSEC survivor’s disclosure (Landers et al, 2017).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations